If you are Kaarty and you know it, clap your hands. Mental wellbeing and Aboriginal youth: an examination of the attitudes and beliefs of 18-25 year olds residing in Perth WA - Webb, Michelle (Curtin University, 2021)
The aims of this research were to explore and share how Indigenous young people (18-25 years) define and understand the broad term ‘mental health’ and to explore what they needed to grow up and stay strong and well. The research process aimed to provide opportunities for young Indigenous adults with a space that is culturally secure and safe in which to explore this. This approach is centred on giving primacy to voices from our communities and framing them in ways that support and nurture our strengths and capacity. What the Storytellers shared in relation to growing up and staying strong and well are centred on the importance of connections to people, Place and Culture and are shared in chapter seven. By identifying existing strengths within families and individuals, these Stories highlight the core importance of relationships for the young people in the project.